Why Children's Hospitals Are Unique and So Essential - Casimir, Georges (Frontiers in Pediatrics, 2019)
Children’s hospitals were created in the 19th century, first in France and then in England. They were designed to provide optimal care to infants, children, and adolescents in a specific environment where parents were admitted and where the special needs of children were catered for. No other system currently offers so many advantages as the multidisciplinary teams with their pediatricians, surgeons, anesthesists, intensive care specialists, and all the allied health professionals who can add their knowledge to the quality of care. From the beginning, they played a major role in caring for socially disadvantaged children. They brought together more than 95% of tertiary care, including cancer care and organ transplantations. They represent the best blend for the study of pediatric medicine and physiology, for high-level preventive medicine, and for research in all fields of pediatrics. This probably explains why they have developed everywhere around the world.